Jilbab pakaian wanita muslimah. Pandangan ulama masa lalu & cendekiawan kontemporer - SHIHAB, M. Quraish (Lentera Hati, 2004)
Jilbab pakaian wanita muslimah. Pandangan ulama masa lalu & cendekiawan kontempore